Terbinafine resistance in Trichophyton mentagrophytes and Trichophyton rubrum in the Czech Republic: A prospective multicentric study - Kolarczyková, Daniela; Lysková, Pavlína; Švarcová, Michaela; Kuklová, Ivana; Dobiáš, Radim; Mallátová, Naďa; Kolařík, Miroslav; Hubka, Vit (Mycoses, 2024)
BACKGROUND: Terbinafine, an allylamine antifungal, is crucial for treating dermatophytosis by inhibiting squalene epoxidase (SQLE) in the ergosterol biosynthetic pathway. However, resistance is emerging, particularly in India and Southeast Asia, but reports of resistance spread worldwide. Despite this, comprehensive studies on terbinafine resistance in Trichophyton are still limited. OBJECTIVES: This research aimed to determine the prevalence of terbinafine resistance in the Czech Republic, with a focus on Trichophyton rubrum and Trichophyton mentagrophytes, and investigate the underlying molecular mechanisms. PATIENTS/METHODS: A total of 514 clinical strains of T. rubrum and 240 T. mentagrophytes collected from four Czech clinical institutions were screened for terbinafine resistance. Molecular investigations included DNA sequencing, specifically the ITS rDNA region and SQLE gene, as well as antifungal susceptibility testing following EUCAST guidelines. RESULTS: While no resistance was observed in T. rubrum, 2.5% of T. mentagrophytes strains exhibited resistance, marked by the F397L mutation in SQLE. Notably, resistance surged from 1.2% in 2019 to 9.3% in 2020 but reverted to 0% in 2021. All resistant strains were identified as T. mentagrophytes var. indotineae. Resistant strains exhibited high MICs for terbinafine (≥4 mg L-1 ) but low MICs to the other seven antifungals tested except for fluconazole. CONCLUSIONS: This study highlights the emergence of terbinafine-resistant T. mentagrophytes strains in the Czech Republic, with the F397L mutation being pivotal. Due to the relatively low resistance level, the current guidelines for dermatomycosis treatment in the Czech Republic remain effective, but ongoing surveillance is essential for timely adaptations if resistance patterns change.
Keywords: Antifungal Agents; squalene epoxidase; terbinafin; Drug Resistance, Fungal; dermatomycosis; Česká republika; anthropophilic dermatophytes; Microbial Sensitivity Tests; antifungální látky; Prospective Studies; Squalene Monooxygenase; prospektivní studie; Czech Republic; Arthrodermataceae; fungální léková rezistence; lidé; Trichophyton; zoophilic dermatophytes; Humans; antifungal resistance; Terbinafine; mikrobiální testy citlivosti; skvalenmonooxygenasa; allylamines